Screening and bioinformatics analysis of cellular proteins interacting with chicken bromodomain-containing protein 2 in DF-1 cells. Issue 6 (2nd November 2021) - Zhou, L.; Han, Y. F.; Yuan, C.; Duan, Z. Q.
ABSTRACT: 1. Bromodomain-containing protein 2 (BRD2) is an important member of the BET protein family, which can specifically bind histone acetylated lysine to participate in gene transcriptional regulation, chromatin remodelling, cell proliferation and apoptosis. The following investigation of cellular proteins interacting with chBRD2 will be helpful in understanding the new functions of chBRD2 and the mechanism of NDV replication. 2. The recombinant eukaryotic expression vector pEGFP-chBRD2 and empty vector pEGFP-C1 were transfected into DF-1 cells to overexpress GFP-chBRD2 and GFP, respectively. GO annotation, KEGG pathway, and protein-protein interaction network were used to analyse the cellular proteins interacting with chBRD2. In addition, one targeted protein was selected to verify its interaction with chBRD2 using fluorescent co-localisation and Co-IP. 3. A total of 225 cellular proteins were identified that potentially interact with chBRD2. GO analysis showed that these play key roles in gene transcriptional regulation, cell cycle and development, immunity and viral infection. Further KEGG pathway analysis showed that these proteins were mainly involved in genetic information processing, immune system, cellular processes and translation. In addition, one targeted cellular protein chicken matrin 3 (chMATR3) was also identified as chBRD2 complex using both fluorescence co-localisation and Co-IP analysis. 4. This study presents the interactome data of chBRD2 protein in DF-1 cells, which provides new information to understand the functions of chBRD2 and new targets for further investigating the replication and pathogenesis of NDV.